Writing in space, 1973-2019 - O'Grady, Lorraine 1934- (Duke University Press, 2020)
Writing in Space, 1973-2019 gathers the writings of conceptual artist Lorraine O'Grady, who for over forty years has investigated the complicated relationship between text and image. A firsthand account of O'Grady's wide-ranging practice, this volume contains statements, scripts, and previously unpublished notes charting the development of her performance work and conceptual photography; her art and music criticism that appeared in the Village Voice and Artforum; critical and theoretical essays on art and culture, including her classic "Olympia's Maid"; and interviews wherein O'Grady maps, expands, and complicates the intellectual terrain of her work. She examines issues ranging from black female subjectivity to diaspora and race and representation in contemporary art, exploring both their personal and institutional implications. O'Grady's writings-introduced in this collection by critic and curator Aruna D'Souza-offer a unique window into her artistic and intellectual evolution while consistently plumbing the political possibilities of art
Keywords: O'Grady, Lorraine -- 1934-; Geschichte 1973-2019; ART / American / African-American; Conceptual art; Words in art; Concept-art; USA; Aufsatzsammlung